Perhitungan Neraca Massa Pada Reception Oil Tank di Stasiun Klarifikasi PKS XYZ Sumatera Utara - Dimas Frananta Simatupang; Darni Paranita; Nuranika Nuranika; Hendra Saputra; Merta Simbolon (Indonesian Journal Publisher, 2023)
Reception Oil Tank (ROT) is a unit at a clarification station that has a function as a temporary storage tank for filtered crude oil from the vibro-separator unit and also to retain heat. In this ROT, the heat provided comes from direct injection of hot steam and steam coils with temperatures ranging from 90-95 0C. This research was conducted with the aim of determining the flow rate of materials into and out of ROT using the principle of mass balance and determining the levels of each component in the oil in ROT before further processing. Based on the results of the mass balance calculation, it was obtained that the flow rate of crude oil entering ROT was 10794.2 kg/hour. The composition content of the materials entering ROT in 10 mL includes 37.6% oil, 26.6% water and 35.8% non-oil solid while the composition levels of materials leaving ROT to CST include 41.6% oil, 27% water, and non-oil solids 31.4%. The oil content has increased during the process that occurs in the ROT at the clarification station.